Effect Of Mulching And Tillage On Yield And Keeping Quality Of Garlic (Allium sativum L.) (Bangladesh Journal of Agricultural Research, 2013)
An experiment was carried out at the Horticulture Farm, Bangladesh Agricultural University, Mymensingh during rabi season of 2006-2007 to study the effects of different thickness of water hyacinth mulch and tillage on the storage life of garlic. The experiment was consisted of five depths of water hyacinth mulch (0, 6, 8, 10, and 12 cm) and two methods of tillage (conventional and zero). It was laid out in the split plot design with three replications. The study revealed that the bulbs from the zero tillage showed the highest storage quality resulting in the lowest weight loss (8.45%), insect infested bulbs (6.67%) as well as rotten bulbs (2.44%) after 150 days of storage. In contrast, bulbs grown under conventional tillage with no mulch and 6 cm thick mulch had the lower storage quality compared to those of other treatment combinations. The result showed that garlic production under zero tillage with 12 cm mulch could be used for better storability. Bangladesh J. Agril. Res. 38(1): 115-125, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15196